(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to analyze the problems of developing halal tourism based on local wisdom from the perspective of economic empowerment of local communities, especially in relation to preventing rejection from the community. Data were collected through qualitative methods with triangulation techniques of observation, interviews, FGD and documentation. The data obtained is then analyzed according to its actual conditions, and then each element of the actual condition is combined to produce conclusions. The results showed that the plan to determine halal tourism, which is set by the government, is expected to be able to be responded to by the local community; Local wisdom of the local community in responding to plans to determine halal tourism in improving economic living standards, can help the economy and tourism development without eliminating existing local wisdom; The results achieved by the community regarding regional economic empowerment in the development of halal tourism, the North Sumatra Provincial Government and related agencies collaborated with each other and provided socialization with the local community. This tourism development is recommended to be continued.